CORPORATE GOVERNANCE CHARACTERISTICS AND CORPORATE SOCIAL RESPONSIBILITY - Meilani Dewinta Kristina Mantiri; Rizky Eriandani (UNIB Press, 2022)
This study aims to analyze the characteristics of corporate governance influencing CSR disclosure in banking. Implementing good corporate governance allows the company's stakeholders to receive accurate and transparent information about the company's internal conditions through CSR disclosure. Thus, good corporate governance can affect the company's relationship with its stakeholders to maintain long-term sustainability. The research sample obtained was 180 companies from banking sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. A multiple linear regression test was used to test the research model. The study results found that foreign ownership, state ownership, size of the board of commissioners, and the proportion of women on the board of commissioners significantly positively affected CSR.Meanwhile, the proportion of foreign members on the board of commissioners is known to have a significant adverse effect on CSR. In addition, the results showed that diffusion ownership, the size of the board of directors, the proportion of women on the board of directors, chairman of the board of directors, chairman of the board of commissioners, and the proportion of foreign members on the board of directors did not affect CSR. However, there are differences in the level of information disclosed. Furthermore, it can be concluded that the characteristics of corporate governance used in this study do not fully affect CSR disclosure in banks. This research enriches the existing literature, considering that the banking sector is often excluded from CSR studies because of its specific legal regulations and perceived small environmental impact. In addition, in developing countries, very few studies still analyze the effect of board characteristics on bank CSR disclosures. Furthermore, this study emphasizes important implications for the banking sector, shareholders, and regulatory bodies